Uso de sistema wetland construído no pós-tratamento de efluente de curtume - Zacarkim, Carlos Eduardo (2006)
Water contamination with heavy metals is a very important problem in the current world. Occurrence of toxic metals in pond and river water affects the lives of local people that depend upon these water sources for their daily requirements. Chromium is one of the toxic heavy metals, which is released into environment in effluents generated from tanneries and other industries. Conventional chemical methods for removal of toxic metals are ineffective when levels of metals in wastewaters are very low (between 10 - 100 ppm). Therefore, use of low cost, natural resources for removal of metal is being preferred over other conventional methods. Many plants have been known to accumulate heavy metals and other nutrients from contaminated waters and can be exploited for polishing of wastewaters. Aquatic macrophytes have been used during the last two decades for water metal removal competing with other secondary treatments, being the principal mechanism for metal uptake adsorption trough roots. As an alternative method, constructed wetlands have emerged as a viable option for addressing a wide range of water quality problems, especially in treating wastewater effluent. In tropical and subtropical regions, because of its abundance and the large biomass produced, the water hyacinth (Eichhornia crassipes) has been studied especially for this purpose. The main objective of the present study was to evaluate two constructed wetland in greenhouse for treating of tannery wastewater effluent, using two autochthonous floating macrophytes Eicchornia crassipes and Salvinia auriculata in order to remediate the contaminated industrial effluent, under natural conditions. The amount of wastewater generated by a tannery industry is ranged 30-50 L per kg of processed animal skins. Around of 10% of all wastewater effluent correspond to initial stage of animal skin processing into leather and 90% corresponding to intermediate and final process such as washing, neutralization and tinged. This work was performed at a 48-m2 greenhouse constructed in the Toledo Campus of the West Paraná State University, using wastewater effluents from a Tannery industry located in Toledo County. The experiences were carried out for three different hydraulic removal time: 4, 6 and 8 days. At each collection time, physic-chemical parameters such as Oxygen Chemical Demand (OCD), Inorganic Phosphorus and Total Kjeldahl Nitrogen (TKN), pH, Dissolved Oxygen (DO) were determined according to chemical standard methods, and Chromium, Sulfur, Aluminium and Iron total concentrations were calculated by PIXE technique. The second wastewater treatment wetland system working with aquatics plants Salvinia was excluded of these experiences due to tannery wastewaters were along the time in presence of different concentrations of contaminants, showing non-reliable results. Also, tannery wastewaters have shown very high concentrations of sulfur. In such conditions, salvinia species started showing toxicity symptoms and began to develop necrosis. On the other hand, the first wetland system working with the water hyacinth showed high contaminants removal percentages for all evaluated parameters